MEMBANGUN PERPUSTAKAAN YANG ISLAMI (Implementasi Prinsip-Prinsip Manajemen Perpustakan Yang Islami) - Ahmad Syawqi (UIN Imam Bonjol Padang, 2020)
This paper aims to explain in full about the application of the concept of library management in accordance to the principles taught in Islam which can be implemented in building an Islamic library. This research used qualitative research methods that are library research (library research) which used books and other literature as the main object with descriptive analysis to provide a clear, objective, systematic, analytical and critical description of the principles. - Islamic library management principles. From the conclusion of the research discussion, it was found that the concept of Islamic library management is always based on the principles and values of monotheism that exist in the Al-Qur'an and Al-Hadith as the main reference that must be practiced in every aspect of life including the application of various Islamic principles in managing. library organization for the good and progress of the people. The application of management principles taught in Islam which can be implemented in building an Islamic library includes aspects of planning, organizing, leadership and supervision. In planning an Islamic library means determining what will be done in the future or achieving something in the future which is based on God's approval is the theological foundation of action. In the process of planning an Islamic library, each individual or group first makes a decision while still paying attention to deliberation and then submits the final provisions to Allah's decision on its success as an attitude of submitting to Allah's provisions. Once planned, the plan is implemented with all the potential and available resources. In organizing an Islamic library it can be said to be solid and good if it has clear characteristics, goals and realities. In leadership in the library, there is a need for good examples and role models, which are displayed by Rasululllah SAW to serve as a personality model for each leader as uswatun hasanah (good role model). In Islamic library supervision, emphasizes the theological awareness of the presence of Allah SWT as the first supervisor in every person, place and situation. This awareness must be cultivated from the depths of monotheism. Even though it cannot be reached with the eye, Allah SWT still sees everything that is visible because Allah knows best.